Implementation of server virualization to build energy efficient data centers - Uddin, Mueen; Shah, Asadullah; Abubakar, Adamu; Adeleke, Imran (Institute of Heat Engineering, Warsaw University of Technology, 2014)
The rapid growth in the size and capacity of data centers driven by a continual rise in the number of servers and other IT equipment is causing an exponential increase in the demand for power. All data centers are plagued by the operational presence of thousands of servers as major components.These servers consume a huge amount of power while performing little in terms of useful work. In an average server environment, 30% of the servers are "zombies" They merely consume power by offering an opportunity to consolidate multiple underutilized volume servers into a single physical server, thereby reducing the physical and environmental footprint of data centers. This paper suggest implementation " server virtualization" to achieve energy efficient data centers. The proposed technique increases the utilization ration of underutilized servers up to 50%, saving a huge amount of power and at the same time reducing the emission of greenhouse gasses.